Peningkatan Manajemen Mutu Bagi UMKM Furniture Bahan Kayu Jati di Kabupaten Deli Serdang - Amrin Mulia Utama; Patar Marbun (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
This activity is a Community Service (PKM) activity organized by the University of Medan Area, Faculty of Economics and Business, Management Study Program which aims to be a tridarma activity of Higher Education by lecturers. In community service with the title Improved Management for Teak Wood Furniture MSMEs. by community craftsmen, lecturers and students of the Faculty of Economics, Medan Area University, Faculty of Economics and Business held on Saturday, July 8, 2023 The objectives of implementing this Community Service include: Increasing capacity and synergy, knowledge, attitudes, and skills in implementing the development of a quality management system. Motivating MSMEs to remain enthusiastic in entrepreneurship. Encouraging the Management Unit to maintain quality and continuity. As an activity of the Tridharma of Higher Education. The output targets of this Community Service program are: MSME units can increase their productivity, be independent, and be environmentally friendly. The quality management system unit can carry out product innovations to produce superior products that are innovative, competitive and sustainable; UMKM Production Units can produce added value for SMEs thereby increasing the welfare of member; Implementation of online marketing. The methods used in achieving the above objectives are increasing capacity building through imparting knowledge, forming attitudes, and skills through training and field practice.